Reliability assessment and economic evaluation of offshore wind farm using stochastic probability - Atallah A.M.; Abdelaziz A.Y.; Ali M.; Saket R.K.; Bharti O.P. (My University, 2025)
This paper shortly introduced the electric power transmission system for offshore wind farms (OWF). The transmission system components are demonstrated. Each component cost and reliability are studied and tabulated. An evaluation of the transmission system reliability of OWF is performed to increase the dependence on the OWF as a power source in the future. Reliability assessment is performed on a proposed site in Zafarana, Egypt and results are tabulated and simulated for different distances from the shore. The cost of the transmission system is studied using the stochastic probability method; optimization is performed on the investment cost, unavailability cost, and ohmic cost losses. Optimization results on the proposed site are done using different electrical power transmission system schemes. Losses due to the wind unavailability and ohmic losses are studied and simulated. © Springer India 2016.